The role of copper in the formation of the Nb3Sn superconducting phase. (April 2023) - Zhang, Zerong; Gao, Zhan; Wang, Yanan; Meng, Jianli; Cheng, Junsheng; Wang, Qiuliang
Abstract: Nb3 Sn has been widely used in high magnetic field facilities due to its excellent superconducting properties. Moreover, copper has become an indispensable constituent element in the fabrication of Nb3 Sn superconductors. However, the role of copper in the formation of the Nb3 Sn phase is still not thoroughly understood. In this work, Nb–Sn–Cu ternary samples with different molar ratios of copper were prepared by sintering elemental Nb, Sn and Cu mixed powders, and the effect of copper on the formation of the Nb3 Sn phase was systematically investigated. It was found that the addition of copper had a significant effect on the formation of Nb3 Sn. When the amount of added copper was small, the formation of the Nb3 Sn phase was efficiently promoted with the aid of the liquid phase, and a high-purity sample of Nb3 Sn could be formed by the transition from the Nb–Sn binary phases. However, at the same time, the bulk samples with a low ratio of copper possessed poor compactness due to the pressure build-up and tin burst generated by the liquid phase during heat treatment. With increasing copper content, the promotion effect became relatively weaker. More high melting temperature Cu–Sn phases were formed, and Nb3 Sn was gradually formed by solid-state diffusion between Nb and the Cu–Sn matrix. Finally, it was found that the sample of Nb:Sn:Cu = 3:1:3 (mol. %) with a grain size of 70–120 nm possessed the highest critical current density due to its high phase purity and fine grain size of Nb3 Sn. Highlights: Small amount of copper addition could efficiently promote the formation of Nb3 Sn phase with the aid of liquid phase. The bulk sample with low ratio of copper possessed a poor compactness due to the pressure build-up and tin burst generated by liquid phase during heat treatment. The sample of Nb:Sn:Cu = 3:1:3 possessed the highest critical current density due to its high phase purity and fine grain size of Nb3 Sn.